Comparative Transcriptome Analysis Reveals the Mechanism by Ethylene and 1-Methylcyclopropene Treatment on the Vase Life of Cut Oncidium hybridum ‘Honey Angle’ - Jingjing Kou; Xueqian Zang; Zirui Mo; Guangwei Wu; Bei Wang; Guopeng Zhu (Horticulturae)
The cut flowers of the Oncidium hybridum cultivar ‘Honey Angle’ are highly regarded for their vibrant floral display, excellent flower quality, and broad commercial applications. However, its postharvest vase life is significantly challenged by wilting, water loss, and color fading, primarily due to ethylene exposure. To clarify the underlying mechanism, we performed treatments with ethylene and ethylene action inhibitor 1-Methylcyclopropene (1-MCP). The petal changes, vase life, and transcriptomic analysis after treatments were investigated. The results revealed that the 1-MCP treatment significantly extended the vase life by upregulating the genes involved in carotenoid synthesis, suppressing the genes related to cell wall degradation and the ethylene signaling pathways. In contrast, the ethylene treatment accelerated senescence by activating the senescence-related genes and increasing ethylene production. Transcriptome analysis identified 960 transcription factors, predominantly from the NAC, WRKY, ERF, bHLH, and MYB families, which were crucial in regulating quality changes during the vase life. A total of 5203 differentially expressed genes (DEGs) were assigned to 19 KEGG pathways including carbohydrate and energy metabolism as well as plant hormone signal transduction. Weighted gene co-expression network analysis (WGCNA) indicated that these DEGs were primarily associated with weight loss, flowering ratio, lightness, maximum petal diameter, and respiration intensity. This research provided valuable insights into the molecular mechanisms of floral senescence and practical guidance for extending the vase life of ‘Honey Angle’ cut flowers.